Analisis Standar Penilaian Pendidikan pada Pendidikan Dasar - Rozana, Della; Maysari, Silfi; Ramadhani, Afifah Fitria; Ananda, Rizki (Lembaga Yasin AlSys, 2023)
The education assessment system is the most important measure for this national education assessment. To assess the progress of the education system, these standards are evaluated by holding a national exam. The national law based on the Ministry of Education and Culture's instruction on abolishing the national exam has had many advantages and disadvantages, especially among teachers. This study considers the National Examination as a very important assessment standard for determining the current educational progress of students so that the government knows and can organize education in accordance with the rights of students according to students, teachers and similar institutions and can monitor learning. The aim is to identify the concept of evaluation in secondary schools, the principles of teacher evaluation in secondary education and teaching, and to identify the principles of evaluating quality, knowledge and skills in secondary education. The method used is the literature review method by collecting information from written sources in the form of books, journals and articles. The findings of this study are that the assessment method is still applied so that it can provide answers related to the scientific method of learning the 2013 curriculum by compiling a methodology, perfecting previous research and research that focuses on considering aspects of knowledge. and carry out a complete assessment of the aspects of character, knowledge and skills, shifting from the teacher to focusing on the student learning process, it is necessary to develop a system for measuring learning outcomes, namely effective assessment, and increasing the orientation of learning assessment for currently learning. process and learning outcomes.